2024
DOI: 10.1039/d3su00382e
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic carbon nitride (g-C3N4) as an emerging photocatalyst for sustainable environmental applications: a comprehensive review

Dhavalkumar Bhanderi,
Pratikkumar Lakhani,
Chetan K. Modi

Abstract: g-C3N4: a sustainable game-changer in photocatalysis. This work explores synthesis, properties, mechanisms, and applications, addresses challenges, and charts future trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Commercially available chemicals were used as received. 1 H-and 13 C NMR spectra were recorded in CDCl 3 using a Bruker AVANCE III 500 MHz spectrometer (Bruker, BioSpin GmbH, Germany) with working frequencies of 500 and 126 MHz, respectively, at 30 °C. Chemical shifts are expressed in parts per million (δ scale) downfield from tetramethylsilane and are referenced to residual protium in the NMR solvent (CHCl 3 : δ7.25 ppm).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially available chemicals were used as received. 1 H-and 13 C NMR spectra were recorded in CDCl 3 using a Bruker AVANCE III 500 MHz spectrometer (Bruker, BioSpin GmbH, Germany) with working frequencies of 500 and 126 MHz, respectively, at 30 °C. Chemical shifts are expressed in parts per million (δ scale) downfield from tetramethylsilane and are referenced to residual protium in the NMR solvent (CHCl 3 : δ7.25 ppm).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Arguably, the development of the photosensitizer is a considerable research challenge as it plays the important role of capturing initial solar irradiation and consequent photoexcited electron transfer through the system to a photochemically unreactive substrate. In the view of light harvesters, inorganic semiconductors (transition-metal oxides or hydroxides and their derivatives); , organic polymeric semiconductors; graphitic materials; metal–organic frameworks with photoresponsive metal ions surrounded with organic ligands; organic dyes; and organometallic complexes are several established divisions. , The value of the photosensitizer increases with the abundance of the material, good photostability and stability in neutral aqueous media, efficient working, and competitive cost. , …”
Section: Introductionmentioning
confidence: 99%
“…Regarding their photocatalytic activity, it was found that pure g-C 3 N 4 exhibited both high MG adsorption and photocatalytic discoloration of MG solutions under dark and illuminated (UV and visible light) conditions, respectively. It is well-known that high π- π interaction between s-triazine units of g-C 3 N 4 and the probe molecule can drive high pollutant removal from water. MG is a triphenylmethane dye consisting of three aryl groups which can strongly interact via π–π interactions with the g-C 3 N 4 . This exposes the molecule to the direct attack of photoinduced h + VB and ROS (Scheme S1).…”
Section: Discussionmentioning
confidence: 99%
“…It is seen in the social sciences, natural sciences (physical and biological), and applied sciences. From the social science perspective, owing to the penetration of this terminology, we now have sustainable anthropology, 88 sustainable archaeology, 89 sustainable economics 90 sustainable geography, 91 sustainable criminology, 92 green chemistry, [93][94][95][96] which includes green solvents, 97 green chemical processes, [98][99][100] sustainable electrochemistry, 101 chemical recycling, 102 sustainable metallurgy, 103,104 sustainable compounds and materials [105][106][107] etc. Other sustainable elds include green ecology, 108 sustainable physics, 109 sustainable microbiology, 110 sustainable engineering, 111 sustainable technology, 112 sustainable agriculture, 113 which has agronomy as one of its strategies.…”
Section: Third Layer: Domain Penetrationmentioning
confidence: 99%